Implementing the Action-Plan Training Model to Enhance Employees’ Competencies: A Hotel Case Study - Boonpektrakul, Ong-Art (ABAC ODI JOURNAL Vision. Action. Outcome, 2014)
Hundreds of hours and millions of dollars are spent to train employees every year in the organization, however, little empirical evidence can be found to demonstrate the transfer of training in workplaces. This study represents a case study in the hotel industry in which a model for the transfer of training knowledge, Action-Plan Training Model, is examined and implemented. Theoretical analysis and multiple data collection methods were used to answer questions regarding the training processes and the utilization of Action-Plan Training Model for twelve months following the program. Five principal research methods, interview, focus groups, questionnaires, observations and documentary analyzes, were used to cast a wide net to ensure that the highest quality data are collected. The results showed that the Action-Plan Training Model is highly effective and contributes to employee performance.